Barriers to pharmacist prescribing: a scoping review comparing the UK, New Zealand, Canadian and Australian experiences. (9th July 2019) - Zhou, Mingming; Desborough, Jane; Parkinson, Anne; Douglas, Kirsty; McDonald, David; Boom, Katja
Abstract: Objectives: Non-medical prescribers, including pharmacists, have been found to achieve comparable clinical outcomes with doctors for certain health conditions. Legislation supporting pharmacist prescribing (PP) has been implemented in the United Kingdom (UK), Canada and New Zealand (NZ); however, to date, Australian pharmacists have not been extended prescribing rights. The purpose of this review was to describe the barriers to PP found in the literature from the UK, Canada, NZ and Australia, and examine the implications of these for the development of PP in Australia. Methods: We conducted a scoping review, which included peer-reviewed and grey literature, and consultation with stakeholders. Sources – Scopus, PubMed and CINAHL; Google Scholar, OpenGrey and organisational websites from January 2003 to March 2018 in the UK, Canada, NZ and Australia. Inclusion criteria – articles published in English, related to implementation of PP and articulated barriers to PP. Key findings: Of 863 unique records, 120 were reviewed and 64 articles were eligible for inclusion. Three key themes emerged: (1) Socio-political context, (2) Resourcing issues and (3) Prescriber competence. The most common barriers were inadequate training regarding diagnostic knowledge and skills, inadequate support from authorities and stakeholders, and insufficient funding/reimbursement. Conclusions: If implementation of PP is to occur, attention needs to be focused on addressing identified barriers to PP implementation, including fostering a favourable socio-political context and prescriber competence. As such, a concerted effort is required to develop clear policy pathways, including targeted training courses, raising stakeholder recognition of PP and identifying specific funding, infrastructure and resourcing needs to ensure the smooth integration of pharmacist prescribers within interprofessional clinical teams.